2015
DOI: 10.3109/15569527.2014.1003267
|View full text |Cite
|
Sign up to set email alerts
|

Electroretinographic and optical coherence tomography findings in breast cancer patients using aromatase inhibitors

Abstract: Our study is the first in the literature investigating the potential effect of AIs on RNFL thickness, optic nerve and macular function in patients using AIs for breast cancer treatment. The principal message of our study is that patients using AIs exhibited a significant decrease in RNFL thickness (average, superior and inferior), retinal response density and visual acuity compared to healthy controls, while VEP findings (both amplitude and peak time of P100) differ significantly as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In addition to this advantage, we also need to be aware of possible side effects. Specifically, aromatase inhibitor use among women with hormone receptor-positive breast cancer was associated with a decrease in retinal nerve fiber layer thickness (37). Through pleiotropy, we can better understand how shared genetic factors between traits influence biological processes, such as drug metabolism, and subsequently, how they may aid in more effective treatments while also preventing negative side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this advantage, we also need to be aware of possible side effects. Specifically, aromatase inhibitor use among women with hormone receptor-positive breast cancer was associated with a decrease in retinal nerve fiber layer thickness (37). Through pleiotropy, we can better understand how shared genetic factors between traits influence biological processes, such as drug metabolism, and subsequently, how they may aid in more effective treatments while also preventing negative side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moschos et al investigated the impact of AIs on macular, retinal, and optic nerve function. The study concluded that AIs significantly decrease retinal nerve fibre layer thickness, retinal response density, and visual acuity [ 10 ]. There has also been evidence of crystalline retinopathy in a patient who was six months into anastrozole treatment [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…Moschos and colleagues 148 evaluated the effects of aromatase inhibitors (AIs) used in patients with breast cancer on peripapillary RNFL thickness, optic nerve and macular function. The study showed that AIs significantly decreased RNFL thickness (overall average, superior and inferior).…”
Section: Review Of Diseasesmentioning
confidence: 99%